Corridor : media architectures in American fiction - Marshall, Kate, 1976- (UPCC book collections on Project MUSE. Literature., 2013)
This book offers a series of conceptually provocative readings that illuminate a hidden and surprising relationship between architectural space and modern American fiction. By paying close attention to fictional descriptions of some of modernity's least remarkable structures, the author discovers a rich network of connections between corridors and novels, one that also sheds new light on the nature of modern media.